Diagnostic challenges of Pityriasis Lichenoides et Varioliformis Acuta (PLEVA) - Abd Rahman, Mohd Aizuddin; Jamani, Nurjasmine Aida; Abdul Halim, Sarah; Zainun, Norsafina (UniKL Royal College of Medicine Perak (UniKL RCMP), 2024)
Pityriasis Lichenoides et Varioliformis Acuta (PLEVA) is an uncommon, inflammatory skin illness typified by erythematous papules that can mimic various dermatological and systemic conditions, making diagnosis difficult. We describe a case of a young adult who presented with generalized erythematous macules and crusted patches across the trunk that progressed to the extremities and scalp. A provisional diagnosis of guttate psoriasis with PLEVA as the differential diagnosis was made after a thorough history and examination. Further evaluation and skin biopsy confirmed the diagnosis of PLEVA through histopathological examination. The lesions subsided after two months of treatment with oral and topical corticosteroids.